Book Review – The Police in War: Fighting Insurgency, Terrorism, and Violent Crime - Sullivan, John P. (International Journal of Police Science, 2024)
Book: David H. Bayley and John M. Perito, The Police in War: Fighting Insurgency, Terrorism, and Violent Crime (Boulder: Lynne Rienner Publishers, 2010). ISBN: 9781588267290 (hardcover); 978162378292 (ebook)